Diagnosis failure of bovine leukosis: serology variation during the peripartum period - Arabe Filho, Marcelo Fagali [UNESP]; Megid, Jane [UNESP]; Carneiro, Deolinda Maria Vieira Filha; Carneiro, Elinton Weinert; Mioni, Mateus de Souza Ribeiro [UNESP] (Springer Nature, 2022)
This study demonstrates the influence of pregnancy on serum diagnosis of enzootic bovine leukosis (EBL), emphasizing the importance of routine testing to maintain herd health. For this, 143 pregnant cows were sampled in duplicate (30 days before and 15 days after calving). For EBL diagnosis, samples were submitted to agar gel immunodiffusion testing (AGID). Different results were observed before and after delivery in seventy-six serum samples (53.15%), indicating variations in the levels of serum globulins in the blood during the peripartum period. Therefore, using a single sample for serological diagnosis during the birth season might not represent the correct infection status of animal health due to physiological variations in antibody concentrations.
Keywords: Enzootic bovine leukosis; Health status; Herd immunity; Immunodiagnostics; Serology